2004
DOI: 10.1590/s0101-81752004000400035
|View full text |Cite
|
Sign up to set email alerts
|

Nycteribiidae (Diptera, Hippoboscoidea) no Sul do Brasil

Abstract: Revista Brasileira de Zoologia 21 (4): 971-985, dezembro 2004

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 11 publications
(13 reference statements)
1
17
0
4
Order By: Relevance
“…In addition to these biogeographical particularities, the region contains a mosaic of vegetation types (Rambo 2005), increasing its importance for studies focusing on the distributions and relationships between these groups. The few studies on bat ectoparasites in southern Brazil include those of Graciolli and Rui (2001), Graciolli (2004) and Rui and Graciolli (2005) in dense Atlantic Forest, and some commentaries in the studies of Guimarães (1941) and Guimarães and D'Andretta (1956).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these biogeographical particularities, the region contains a mosaic of vegetation types (Rambo 2005), increasing its importance for studies focusing on the distributions and relationships between these groups. The few studies on bat ectoparasites in southern Brazil include those of Graciolli and Rui (2001), Graciolli (2004) and Rui and Graciolli (2005) in dense Atlantic Forest, and some commentaries in the studies of Guimarães (1941) and Guimarães and D'Andretta (1956).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the rates of parasitism (prevalence, intensity or mean abundance of infestation) of some bat fly species on their hosts in different parts of Brazil (Komeno and Linhares 1999, Graciolli and Rui 2001, Bertola et al 2005, Rui and Graciolli 2005, Rios et al 2008 and countries in the Americas (Gannon and Willig 1995 in Puerto Rico;Guerrero 1996 in Peru;ter Hofstede and Fenton 2004 in Belize;Dick et al 2003 in the USA). Only two of these studies (Graciolli andRui 2001, Rui and were carried out in Rio Grande do Sul. In spite of this increased effort, the need for more studies on this question still remains, in order better to understand the ecology of bat fly parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…Species of the Streblidae family are common ectoparasites in neotropical bat populations (WENZEL 1976, GUERRERO 1996, MOURA et al 2003, GRACIOLLI 2004. However, there are no records in the literature about the presence of ectoparasites in the feces of N. leporinus.…”
Section: Discussionmentioning
confidence: 99%
“…Piscivoria; sardinha. GRACIOLLI 2004). However, studies involving the carnivorous or piscivorous species are very limited (NOWAK 1994).…”
mentioning
confidence: 99%
“…Pela facilidade de captura e de manipulação do hospedeiro e a melhor visualização dos dípteros sobre o corpo de morcegos, vários artigos têm sido publicados sobre a ocorrência de dípteros ectoparasitos de morcegos no Brasil (por exemplo, Dias et al, 2009;Graciolli & Bianconi, 2007;Graciolli et al, 2010;Lourenço & Esbérard, 2011;Aguiar & Antonini, 2011). Além disso, artigos recentes sobre a taxonomia dessas famílias de dípteros ectoparasitos de morcegos têm facilitado a identificação dos gêneros e das espécies e despertado o interesse de estudantes e pesquisadores (Dick & Miller, 2010;Graciolli, 2004;Graciolli & Azevedo, 2011;Graciolli & Carvalho, 2001a;2001b;Graciolli & Dick, 2012;Graciolli & Moura, 2005), enquanto importantes contribuições sobre a taxonomia de hipoboscídeos neotropicais são mais escassos (Graciolli & Carvalho, 2003;, sendo os mais importantes publicados a mais 40 anos (Bequaert, 1954;Maa, 1969;Peterson & Maa, 1970), por exemplo.…”
Section: Lipoptena Mazamae (Rondani 1878) Ozotocerosunclassified